Counseling of the Storytelling Method with Dental Phantom Media on Toothbrushing Skills in Preschool Children - Silvia Prasetyowati; Tara Tuhfatul Ayu Bakta; Agus Marjianto; Anshad Ansari (International Journal of Advanced Health Science and Technology, 2023)
Preschool-age children are an age group that is relatively high in caries. The prevalence of caries in preschool-aged children in 2018 was 93%. The most effective way to prevent dental health problems, especially cavities, is to brush your teeth and promote dental health using methods that are on target. Storytelling is a therapeutic process that positively and effectively influences preschoolers' learning comprehension. Storytelling helps children learn new things and creates a comfortable learning environment. This study aims to analyze the effect of counseling using the storytelling method with dental phantom media on the teeth-brushing skills of preschoolers. The type of research used is Quasi Experiment with pre and post-test design. The population in this study were 32 students of Kindergarten Islam Plus Al Haqiqi Surabaya. Methods of data collection using observation sheets. The data analysis technique uses the Wilcoxon test. The results of the study showed that counseling on the storytelling method with dental phantom media affected the teeth brushing skills of preschoolers at the Islam Plus Al Haqiqi Kindergarten in Surabaya. Preschool-age children are an age group that is relatively high in caries. The prevalence of caries in preschool-aged children in 2018 was 93%. The most effective way to prevent dental health problems, especially cavities, is to brush your teeth and promote dental health using methods that are on target. Storytelling is a therapeutic process that positively and effectively influences preschoolers' learning comprehension. Storytelling helps children learn new things and creates a comfortable learning environment. This study aims to analyze the effect of counseling using the storytelling method with dental phantom media on the teeth-brushing skills of preschoolers. The type of research used is Quasi Experiment with pre and post-test design. The population in this study were 32 students of Kindergarten Islam Plus Al Haqiqi Surabaya. Methods of data collection using observation sheets. The data analysis technique uses the Wilcoxon test. The results of the study showed that counseling on the storytelling method with dental phantom media affected the teeth brushing skills of preschoolers at the Islam Plus Al Haqiqi Kindergarten in Surabaya.